Investigation of the Right and Left Brain Hemisphere Capabilities among gifted students with and without learning disabilities - fateme dfsdfsdf; sdfsadf sdfasd; csadfs fdasdf; gdgf gdf (Ravānshināsī-i Afrād-i Istis̠nāyī, 2016)
The purpose of the present study was to investigate right and left brain hemispheres’ capabilities in gifted students with and without learning disabilities. This causal-comparative study was conducted on 23 gifted students with learning disabilities (17 girls and 6 boys) and 29 gifted students (17 girls and 12 boys) who studied in third to fifth grades of elementary school in Shiraz. Purposive sampling was used to identify participants. Wechsler Intelligence Scale for Children-IV (2003), Screening Inventory Reading Test (2009), Torrance Creative Thinking Test, Keymath Test (1999), Reading and Dyslexia Test (2005) and The Kingore Observation Inventory (2001) were used as formal tools in this study. In addition, the state achievement tests, workbooks and teacher's comments were considered. The data in this study were analyzed by descriptive and inferential statistics. The results showed that there were significant differences between two groups in creativity, sense of humor, visual processing speed, fluid intelligence, and nonverbal fluid reasoning that relate to the capability of the right hemisphere (p< 0. 01). All abilities of the left hemisphere, there were a significant differences among gifted students and gifted students with learning disorders (p